2020
DOI: 10.1186/s12995-020-00268-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical risk and safety awareness, perception, and practices among research laboratories workers in Italy

Abstract: Introduction: Exposure to chemical compounds occurs in numerous occupational settings, among which the research and healthcare laboratories have not been adequately investigated. These settings are characterized by an extreme variability of the used compounds and by the frequent turnover of young researchers. The main objectives of the study were to explore the occupational exposure to hazardous chemical substances among research laboratory workers; to assess their awareness and perceptions regarding chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…Different components (deliberative, affective, or experiential [20]), and many factors are involved in the formation of risk perceptions, including literacy and numeracy levels [21], dispositional situations [22], personal experiences, information availability and presentation [23], and physical and psychological well-being of the exposed individual [24]. Health risk perception of chemical exposure has been assessed in numerous settings and targeted populations (e.g., drinking water quality [25], chemical household products [24,26], food additives and contaminants [27], research laboratory workers [28], or recreational beach use by children [29]), as a starting point, to build-up effective risk communication strategies and public health interventions, which ultimately may lead to risk perception and health behaviour changes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Different components (deliberative, affective, or experiential [20]), and many factors are involved in the formation of risk perceptions, including literacy and numeracy levels [21], dispositional situations [22], personal experiences, information availability and presentation [23], and physical and psychological well-being of the exposed individual [24]. Health risk perception of chemical exposure has been assessed in numerous settings and targeted populations (e.g., drinking water quality [25], chemical household products [24,26], food additives and contaminants [27], research laboratory workers [28], or recreational beach use by children [29]), as a starting point, to build-up effective risk communication strategies and public health interventions, which ultimately may lead to risk perception and health behaviour changes [20].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on chemical exposure in a research laboratory in Italy yielded a response that 54.4% felt very exposed to chemical risk [13]. Our results revealed a relatively low ratio of perceived chemical risk (17.4%).…”
Section: Discussionmentioning
confidence: 56%
“…Protective training is also recommended to improve health care nurses' perceptions of the risks associated with ADs. Papadopoli et al 1 reported that a higher perception of risk is related to a greater likelihood of behaving safely; therefore, investigation of perceptions of risk is very useful for predicting behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown an increase in the potential risks due to occupational exposure to ADs. 1,2 Nurses are the main group exposed to these drugs in hospitals. They are typically exposed while administrating ADs.…”
Section: Introductionmentioning
confidence: 99%